Association between inflammatory markers and serum paraoxonase and arylesterase activities in the general population: a cross-sectional study - Christa Meisinger (Lipids in Health and Disease, 2021)
Abstract Background Recent studies focused on modulating factors of paraoxonase-1 (PON1) activity. In some studies the association between pro-inflammatory markers and PON1 activity was examined, but so far no population-based investigations on this issue have been conducted. The present study investigated the relationships between the pro-inflammatory markers tumor necrosis factor (TNF)-α, leptin, interleukin (IL)-6, and high-sensitive C-reactive protein (hs-CRP) and paraoxonase and arylesterase, two hydrolytic activities of PON1, in the population-based Bavarian Food Consumption Survey II. Methods Based on 504 participants (217 men, 287 women), the relationship between the pro-inflammatory markers and the outcomes paraoxonase and arylesterase activities were investigated using multivariable linear models. Results Circulating plasma levels of leptin (P-value < 0.0001), hs-CRP (P-value = 0.031) and IL-6 (P-value = 0.045) were significantly non-linearly associated with arylesterase activity. Leptin levels were also significantly associated with paraoxonase activity (P-value = 0.024) independently from confounding factors, including high-density lipoprotein (HDL) cholesterol. With increasing levels of these inflammatory parameters, arylesterase and paraoxonase activities increased; however, at higher levels (> 75th percentile) the activities reached a plateau or even decreased somewhat. After Bonferroni-Holm correction, only leptin remained non-linearly but significantly associated with arylesterase activity (adjusted overall P-value < 0.0001). Neither age nor sex nor obesity modified the associations. No association was found between TNF-α and paraoxonase or arylesterase activity. Conclusions The present findings suggest that in persons with very high levels of inflammation, PON1 activity may be impaired, a fact that might subsequently be accompanied by a higher risk for cardiometabolic diseases. Whether or not the measurement of PON1 activity in combination with a lipid profile and certain inflammatory markers could improve the prediction of cardiometabolic diseases in middle-aged individuals from the general population should be evaluated in clinical studies.